Validity Of Electronic Student Worksheets (E-LKPD) Problem-Based On Environmental Pollution Material - Dwi Septiwiharti; Nadrah Nadrah; Horas Tua Nopriadi Tampubolon; Reno Francius Simanullang; Insenalia sampe roly Hutagalung (PT. TAROMBO RESEARCH DEVELOPMENT pak, 2026)
The use of less interesting student worksheets can reduce student interest and participation in learning activities. For this reason, worksheets are needed to fulfill these needs. Along with the development of technology, student worksheets can be created in digital form. Electronic worksheets (E-LKPD) not only contain material, but also video material, animations, assignments and other activities that are expected to attract students to be active in learning activities. This study aims to determine the validity of problem-based E-LKPD on environmental pollution materials. The research method used is the Research and Development with a 4-D model (Define, Design, Development, Disseminate) which is then limited to a 3-D model without a deployment stage. The validity test was carried out by three expert validators, namely media experts, material experts and biology subject teachers at MA Muslimin Cipeundeuy. The results showed that the percentage value of problem-based E-LKPD on environmental pollution material from media experts was 75% with the feasible category, the assessment of material experts was 74% with the decent category and biology subject teachers were 92% with the very decent category. The overall validity percentage is 80% and is included in the decent category. Thus, problem-based ELKPD on environmental pollution material developed is suitable for use in learning activities